Infuence of Self-Creativity and Social Media Use on Digital Entrepreneurial Intention among Students at the University of Lampung - Putri Adinda Miranti; Aida Sari; Mudji Rachmat Ramelan (International Journal of Scientific Multidisciplinary Research, 2024)
Lampung University aims to produce high-quality, competitive graduates who are quickly absorbed by the labor market or become entrepreneurs, in line with its motto "Working and Innovating for the Nation." This research investigates the influence of self-creativity and social media use on digital entrepreneurial intentions among University of Lampung students. The study employs a quantitative method with a Likert-scale questionnaire, targeting undergraduate students from the 2020-2022 cohorts, with a sample size of 100 students. Data analysis was conducted using descriptive analysis and SmartPLS 4.0. Findings indicate that both self-creativity and social media use positively and significantly impact digital entrepreneurial intentions. Moreover, social media use also moderates the relationship between self-creativity and digital entrepreneurial intentions, enhancing the effect of self-creativity on students' entrepreneurial aspirations. These results highlight the importance of fostering creativity and leveraging social media to encourage entrepreneurship among students